Light of India or message of Mahatmaji - M S Deshpande; DESHPANDE (M S) (Ahmedabad: Navajivan Publishing House, 1978)
Light of India or Message of MahatmajiThe Light of India or Message of Mahatmaji is an original effort of Shri M.S. Deshpande to construct and present as one whole, Gandhijis philosophy of life - the Goal as well the Means to attain it. Gandhiji has written voluminously and on a variety of subjects in all matters and all aspects touching our life. It is not possible for every reader to go through the whole and cull out the essence, in a co -ordinated form, for his guidance. Shri Deshpande has attempted this and I believe pretty successfully. I believe the title Light of India is taken from the well-known Light of Asia. Looking to the intrinsic value of the philosophy and its acknowledgment, practically by the whole world, I should have preferred Light of the World. But I have no quarrel with the author for the title. Whatever limitations the word of India may imply, there is no doubt, that whosoever reads it does get Light.
Keywords: Humanity; Soul; God; Religions; Prayer; Swadeshi; Satyagraha